VD_FINDINFO HC / 2014 / 56 vom 18. Dezember 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, REJET DE LA DEMANDE | 163 al. 1 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH)